Determination of stress state based on coupling characteristics of load/unload response ratio and outgoing longwave radiation before large earthquakes - Lei, Yu; Jianyong, Li; Chen, Yu; Haizhen, Zhang; Dequan, Hong; Weiyu, Ma (Frontiers in Earth Science, 2024)
The Load/Unload Response Ratio (LURR) is a seismic prediction method based on the dynamic evolution of the stress-strain relationship of rocks. By adopting Benioff strain as the response indicator, an in-depth analysis was conducted on the LURR anomalies within 400 km of the epicenter and its surrounding areas before the Ms7.4 earthquake in Madoi, Qinghai Province, on 22 May 2021. The analysis revealed that the LURR value peaked 1 month before the earthquake and then declined within half a month, indicating that the rock medium in the seismic gestation area was approaching the end of its yielding phase. Further investigation using the Outgoing Longwave Radiation (OLR) data from the National Oceanic and Atmospheric Administration (NOAA) satellite was conducted to study the short-term and imminent anomalous evolution of ground longwave radiation values after the high values declined (from May 14 to 25). The results showed that, spatially, significant and continuous OLR anomalies were observed only in the northern area of the epicenter before the earthquake, and these anomalies exhibited a trend of expanding towards the epicenter. Temporally, the entire anomalous evolution process can be divided into six phases: initial warming, anomaly expansion, peak intensity, anomaly weakening, earthquake occurrence, and anomaly disappearance. To validate this finding, the spatiotemporal evolution characteristics of LURR and OLR within 300 km of the epicenter and its surrounding areas before the Ms6.4 earthquake in Yangbi, Yunnan Province, on 21 May 2021, were analyzed, and similar patterns were found. These results suggest that the high LURR value before its decline may mark the end of the rock medium’s yielding phase, and OLR data can reflect, to some extent, the state of tectonic stress accumulation along active faults in a critical condition. A comprehensive study of the anomalous evolution characteristics of these two physical parameters before the earthquake is not only conducive to the continuity from long-term to short-term forecasts but also of great significance for more accurately assessing the trend of seismic activity.